ANALISIS SWOT PADA STRATEGI PERSAINGAN USAHA MINIMARKET MADINA PURBARATU KOTA TASIKMALAYA - Yayang Primadona; Yusep Rafiqi (JURNAL EKONOMI SYARIAH, 2019)
In choosing the right competitive advantage strategy to be applied by a business,businessmen need to look at market conditions and assess their position in the market. This can be done by analyzing the business environment, both the external environment and the internal environment, usually called SWOT analysis. The purpose of this research is to formulate the most appropriate competitive strategy for to be applied in the future. In this research the author uses descriptive qualitative method with data collection techniques through interview, observation and documentation. Primary data collection is done through in-depth interviews with informants in this study, namely including Madina managers, Madina employees, Madina consumers, Madina suppliers and local governments Purbaratu Tasikmalaya. While secondary data is collected through literature studies, research journals and an overview of research objects, the structure and vision and mission of the company obtained directly from the Madina Purbaratu Tasikmalaya minimarket. The research method used is a qualitative descriptive analysis method with SWOT anlysis. From the results of the IFAS and EFAS analysis the company position is in quadrant 1. From the quadran the recommended strategy is an aggressive/progressive strategy. Then from matrix SWOT the right alternative strategy options that can be applied in Madina in the future is the SO strategy by maintaining the company’sstrengths, minimizing weaknesses and avoiding threats seen from the company’s internal and external factors analyzed through the SWOT matrix